2017
DOI: 10.3171/2016.4.jns152934
|View full text |Cite
|
Sign up to set email alerts
|

Changing of the guard: reducing infection when replacing neural pacemakers

Abstract: OBJECTIVE Infection of deep brain stimulation (DBS) hardware has a significant impact on patient morbidity. Previous experience suggests that infection rates appear to be higher after implantable pulse generator (IPG) replacement surgery than after the de novo DBS procedure. In this study the authors examine the effect of a change in practice during DBS IPG replacements at their institution. METHODS Starting in January 2012, patient screening for methicillin-resistant Staphylococcus aureus (MRSA) and, and wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 42 publications
4
25
0
Order By: Relevance
“…Our study demonstrates lower infection rates than reported historically in the literature (up to 25%) after both DBS implantation (3%) IPG replacement (0.8%) surgeries [2-5]. However, our study shows similar infection rates after implantation surgery compared to Abode-Lyamah et al [2] which reported an infection rate of 3.7% and similar infection rates after IPG replacement compared to Pepper et al [9] which had an infection rate of 0. In Abode-Lyamah et al infection rates were higher during cases without use of intra-operative vancomycin powder use (9.7% versus 3.3%) but was not statistically significant after controlling for sex [2].…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Our study demonstrates lower infection rates than reported historically in the literature (up to 25%) after both DBS implantation (3%) IPG replacement (0.8%) surgeries [2-5]. However, our study shows similar infection rates after implantation surgery compared to Abode-Lyamah et al [2] which reported an infection rate of 3.7% and similar infection rates after IPG replacement compared to Pepper et al [9] which had an infection rate of 0. In Abode-Lyamah et al infection rates were higher during cases without use of intra-operative vancomycin powder use (9.7% versus 3.3%) but was not statistically significant after controlling for sex [2].…”
Section: Discussionsupporting
confidence: 48%
“…Vancomycin powder use was shown to increase risk of infection after electrode implantation surgery (Relative Risk 5.5080, p = 0.02063). This is in contrast to studies that reported a decrease in infections from 8.5% to 0% after MRSA screening and treating prior to IPG replacement as well as using intra-operative vancomycin powder during surgery [9]. Atchley et al also showed that use of intra-operative vancomycin powder did not decrease infections during IPG surgery [10].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…They postulated that the fibrous capsule that surrounds the IPG prevents an adequate inflammatory response to infection. But, the same group recently published a reduction in the rate of infection from 8.5% to 0% after IPG replacement when using a protocol that included screening for MRSA colonization and intraoperative, topical vancomycin/saline wash . Similar to the findings in our study, there was no increased risk of infection in replacement surgeries in the prospective cohort.…”
Section: Discussionsupporting
confidence: 88%
“…Postoperative and late infections related to skin erosion are a major drawback in functional neurosurgery, since these almost always require hardware removal to obtain infection control [20, 24-30, 35, 36]. Consequently, interruption of the neuromodulation therapy and repeated surgical procedures imply suffering for patients and relatives.…”
Section: Discussionmentioning
confidence: 99%